Short synthesis and antiviral evaluation of C-fluoro-branched cyclopropyl nucleosides - Oh, Chang Hyun; Hong, Joon Hee (TAYLOR & FRANCIS INC, 2007)
A series of novel fluorocyclopropyl nucleosides were synthesized using the Simmons-Smith reaction as a key reaction starting from 1,3-dihydroxyacetone. All the nucleosides synthesized were assayed against several viruses. Among the compounds synthesized, the 5-fluorouracil analogue 15 showed significant anti-HCMV activity (9.22 mu M).
Keywords: ANALOGS